Beyond patient-centered care: Enhancing the patient experience in mental health services through patient-perspective care - Timothy Carey (The Beryl Institute, 2016)
Delivering mental health services as patient-centered care has been an international priority for more than 50 years. Despite its longevity there is still not widespread agreement regarding how it should be defined or how it should guide the delivery of services. Generally, though, prioritizing the patient's values and preferences seem to be at the core of this particular approach. It is not clear, however, that services attend to patient values and preferences as closely as they should. Terms such as "treatment resistant" and "noncompliant" seem to belie an attitude where the therapist's opinion is privileged rather than the patients. To improve the effectiveness and efficiency of mental health services a move from patient-centered care to patient-perspective care is recommended. An attitude of patient-perspective care would require service providers recognizing that help can only ever be defined by the helpee rather than the helper. A patient-perspective service that was structured around the preferences and perspectives of patients might finally help to end the long-term suffering of many people who experience mental health problems.